Inhibited complete folding of consecutive human telomeric G-quadruplexes. Issue 4 (30th January 2023) - Kristoffersen, Emil Laust; Coletta, Andrea; Lund, Line Mørkholt; Schiøtt, Birgit; Birkedal, Victoria
Abstract: Noncanonical DNA structures, termed G-quadruplexes, are present in human genomic DNA and are important elements in many DNA metabolic processes. Multiple sites in the human genome have G-rich DNA stretches able to support formation of several consecutive G-quadruplexes. One of those sites is the telomeric overhang region that has multiple repeats of TTAGGG and is tightly associated with both cancer and aging. We investigated the folding of consecutive G-quadruplexes in both potassium- and sodium-containing solutions using single-molecule FRET spectroscopy, circular dichroism, thermal melting and molecular dynamics simulations. Our observations show coexistence of partially and fully folded DNA, the latter consisting of consecutive G-quadruplexes. Following the folding process over hours in sodium-containing buffers revealed fast G-quadruplex folding but slow establishment of thermodynamic equilibrium. We find that full consecutive G-quadruplex formation is inhibited by the many DNA structures randomly nucleating on the DNA, some of which are off-path conformations that need to unfold to allow full folding. Our study allows describing consecutive G-quadruplex formation in both nonequilibrium and equilibrium conditions by a unified picture, where, due to the many possible DNA conformations, full folding with consecutive G-quadruplexes as beads on a string is not necessarily achieved.